Effect of Tissue-Selective Estrogen Complex on Hip Structural Geometry in Postmenopausal Women: A 12-Month Study - Kim, Bo Mi; Kim, Sung Eun; Lee, Dong-Yun; Choi, DooSeok (Frontiers in Endocrinology, 2021)
Background Hip structural analysis (HSA) is a method for evaluating bone geometry reflecting bone structural and biomechanical properties. However, tissue-selective estrogen complex (TSEC) treatment effects on HSA have not been investigated. Objective This study was performed to evaluate the effect of TSEC treatment on hip geometry in postmenopausal Korean women. The treatment was given for 12 months, and hip geometry was measured by HSA. Materials and Methods A total of 40 postmenopausal women who received TSEC containing conjugated estrogen 0.45 mg and bazedoxifene 20 mg for treating vasomotor symptoms were included in this retrospective cohort study. The changes in bone mineral density and parameters of HSA including the outer diameter, cross-sectional area, cross-sectional moment of inertia, cortical thickness, section modulus, and buckling ratio as determined by dual-energy X-ray absorptiometry were compared before and after 12 months of TSEC treatment. Results Mean age and years since menopause were 55.1 and 4.5 years, respectively. Total hip bone mineral density significantly increased by 0.74% after treatment (P=0.011). The changes in HSA were mainly demonstrated in the narrow femoral neck: cross-sectional area (P=0.003) and cortical thickness (P<0.001) increased significantly. For the shaft region, only SM decreased significantly after treatment (P=0.009). However, most parameters did not change significantly with TSEC treatment in the intertrochanteric and shaft regions. Conclusions Our findings demonstrate that 12 months of TSEC treatment could improve bone geometry as measured by HSA. The findings suggest that TSEC might be an interesting option for the prevention of fracture as well as osteoporosis in postmenopausal women.